Peran Guru Bimbingan Konseling Dalam Membimbing Siswa di Madrasah Tsanawiyah Al-Ridha Medan Marelan - Nanda Satria; Syahrul Sitorus; Ali Asmul (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Guidance and counseling teachers have a very important role in shaping the character and character of individual students. To achieve successful implementation of guidance and counseling is very closely related to the management of guidance and counseling in schools. The purpose of this study was to get a clear picture of the program and implementation of guidance and counseling as well as the obstacles of guidance and counseling teachers in coaching students at MTS Ar Ridha Medan Marelan. This research is a descriptive qualitative research. Data collection methods were carried out through observation, interviews, documentation. The research subjects were supervising teachers and school principals and 6 students. The results showed that the form of the guidance and counseling program at MTS Ar Ridha Medan Marelan included individual counseling, information services, and group counseling. Guidance and counseling activities carried out by guidance and counseling teachers have had a pretty good impact, this can be seen from the behavior of students at MTS Ar Ridha Medan Marelan. Obstacles in the implementation of guidance and counseling services are the lack of facilities because MTS Ar Ridha is a waqf from the surrounding community.